Toward Integration of the Niche Diversity Hypothesis With Other Explanations for Personality Covariation: Reply to Međedović's (2019) Commentary on Lukaszewski et al. (2017). Issue 4 (May 2020) - Lukaszewski, Aaron; Gurven, Michael; von Rueden, Christopher R.; Smaldino, Paul
The hypothesis of a human-universal personality structure is undermined by cross-cultural studies in small-scale societies. To explain cross-population differences in patterns of behavioral covariance, we proposed the niche diversity hypothesis, which holds that the degree of behavioral covariation within a population is inversely related to the number and diversity of niches within its socioecology. This hypothesis is formalized as a computational model, and its predictions have been supported empirically. Herein, we respond to several important issues regarding this line of research that were raised in a recent commentary: (1) the study of specific behavioral syndromes should be integrated into the niche diversity model; (2) environmental harshness might alternatively explain our cross-cultural findings regarding effects of niche diversity; and (3) better definitions of behavioral traits are needed for future research. We conclude that the niche diversity hypothesis can be integrated with other explanations for cross-cultural differences in personality covariation.